PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG, DAN PERPUTARAN MODAL KERJA TERHADAP NILAI PERUSAHAAN - Cendy Chandra, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research to determine the effect of profitability, leverage and working capital turnover to firm value. This research uses a simple random sampling method so that the selected sample of 52 companies from a population of 60 manufacturing companies listed in the Indonesia Stock Exchange for the year 2014-2018. This research used the EVIEWS program version 9.0. The result based on t test indicate that profitability has a positive effect on firm value, leverage has a positive effect on firm value, while Working Capital Turnover has a negative effect on firm value.